Evaluation of productive performance of cattle in dairy pocket area of Chitwan and Nawalparasi Districts - Paneru, U.; Sharma, M.; Kolachhapati, M. R.; Shrestha, B. S. (Journal of the Institute of Agriculture and Animal Science, 2018)
A study was conducted in major milk pocket area of Chitwanand Nawalparasi districts with the objective of assessing productive performance of dairy cattle reared in those areas. The study also aimed at categorizing the breed based on its breeding value to determine the most elite cow of different breeds.Four years of data send obtained from Animal Breeding Division in the period between (2008-2012) under the Dairy Cattle Improvement Program were reviewed and analyzed. Altogether, 18316 test day records of 728 animals of 172 herds were considered for evaluation. Results of the above study revealed that the overall least square mean and standard errors (LS mean and SE) of Lactation Milk Yield (LMY), fat percentage, and protein percentage were 2841±84.95 kg, 4.43±0.66 % and 3.33±0.1 %, respectively. Moreover, the study also revealed that breed had significant effect on milk yield (p<0.001), protein percentage (p< 0.01) and Fat percentage (p< 0.001). In addition, top dairy cattle are ranked based on its breeding value on productive parameters. Results of the above study suggested that animal of higher breeding value and it's offspring need to be promoted for better productivity in farmer managed condition of Nepal. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 207-212